Dampak Penggunaan Chatgpt Terhadap Kemampuan Komunikasi Tulisan Mahasiswa Dalam Mata Kuliah Bahasa Indonesia - Sasmika Dewi, Ni Putu (IAHN Gde Pudja Mataram, 2025)
The use of ChatGPT has become a new habit among university students, especially when they work on assignments for Indonesian language courses. This study looks closely at how the technology influences first-semester students who are still in the early stage of developing their writing skills. Using a qualitative approach, the research involved classroom observation, short interviews, and a review of several student writing samples. The findings show that many students rely on ChatGPT to generate initial ideas or simply to help them begin their first paragraph. For some of them, the tool makes their writing appear more organized. However, when they are asked to write without any assistance, they tend to work slowly, hesitate, and produce various basic errors, particularly in sentence structure, word choice, and paragraph coherence. These patterns suggest that technological assistance does not automatically support the growth of writing ability. Beneath the convenience offered by AI tools, students still need adequate digital literacy skills to evaluate, adjust, and refine AI-generated text according to their own understanding. Without this ability, the use of ChatGPT may actually hinder the development of written communication skills, which should ideally be strengthened from the beginning of their academic journey.